Gene regulatory network inference during cell fate decisions by perturbation strategies - Hu, Qing; Lu, Xiaoqi; Xue, Zhuozhen; Wang, Ruiqi (NPJ systems biology and applications, 2025)
With rapid advances in biological technology and computational approaches, inferring specific gene regulatory networks from data alone during cell fate decisions, including determining direct regulations and their intensities between biomolecules, remains one of the most significant challenges. In this study, we propose a general computational approach based on systematic perturbation, statistical, and differential analyses to infer network topologies and identify network differences during cell fate decisions. For each cell fate state, we first theoretically show how to calculate local response matrices based on perturbation data under systematic perturbation analysis, and we also derive the wild-type (WT) local response matrix for specific ordinary differential equations. To make the inferred network more accurate and eliminate the impact of perturbation degrees, the confidence interval (CI) of local response matrices under multiple perturbations is applied, and the redefined local response matrix is proposed in statistical analysis to determine network topologies across all cell fates. Then in differential analysis, we introduce the concept of relative local response matrix, which enables us to identify critical regulations governing each cell state and dominant cell states associated with specific regulations. The epithelial to mesenchymal transition (EMT) network is chosen as an illustrative example to verify the feasibility of the approach. Largely consistent with experimental observations, the differences of inferred networks at the three cell states can be quantitatively identified. The approach presented here can be also applied to infer other regulatory networks related to cell fate decisions.